Children's environmental citizen science: Stakeholders' experiences and perceptions - Catherine Wilson; Sarah Mills; Paul J. Wood (People and Nature)
Abstract Compared to our understanding of adult participation in environmental citizen science (CS), the current literature on child engagement is limited. As adult stakeholders may control children's access to environmental CS (through recruitment strategies, resource provision or as gatekeepers), it is important to understand their experiences and perceptions of engaging children in environmental CS. Semistructured online interviews were conducted with 26 stakeholders of environmental CS. Stakeholders were individuals and organisations that ran or facilitated projects or used environmental CS data. Template thematic analysis was used to analyse the interview materials. This research found that the interviewees were generally positive about the engagement of children in environmental CS, with most stakeholders having equal trust in the data collected by adults and children. Six factors were identified that should be considered when engaging children in environmental CS compared to adults. These were (1) purpose of the project, (2) safety of child participants, (3) supervision of child participants, (4) knowledge and cognitive abilities, (5) attitude and behaviour and (6) commitment to the project. A novel framework for citizen scientists' outcomes, with a focus on children, was developed based on stakeholders' perceptions and experiences. The categories included within this framework were educational, environmental, scientific, well‐being, societal, social and career outcomes. Stakeholders perceived that children could contribute to and benefit from environmental CS, which has positive implications for research and practice across different organisational contexts and sectors of society. The six factors perceived as important considerations when involving children in environmental CS can help practitioners engage young people, creating a more inclusive approach to environmental CS. The development of a framework in this research, which highlights the individual and societal outcomes of environmental CS and specifically focuses on children, emphasises outcomes that had been overlooked in previous frameworks and research, providing clear direction for future project evaluations. Read the free Plain Language Summary for this article on the Journal blog.